The preserving of the physiological functions (Fiep Bulletin - online, 2015)
The Purpose of gymnastics is to preserve – eventually train – the physiological functions, both the physical and the mental. The factors which  destroy the natural functions are diseases arising from overstrain and wear and tear on the muscles of the skeletal system, often concealed behind the diagnoses of neurosis and rheumatism.
Keywords: .